Victims consigned to oblivion - Manrique de Lara Seminario, Jorge (2013)
This article studies people relegated to invisibility: the LGTB (lesbians, gays, transsexuals and bisexuals) from constitutional and international law point of view. Thoughts will be focused on transsexuals and their rights to be treated according to an early internalized gender and some rights emerged from this treatment. Peruvian State role in this subject and the existing challenges will also be analyzed in the same way.